Resilience Development through Counseling Programs: Stress Coping Skills - Sutrisno Sutrisno; Felipe Souza; Bruna Costa; Ilham Mirsal (Yayasan Adra Karima Hubbi, 2025)
Stress is a prevalent issue impacting individuals’ mental health and well-being, requiring effective interventions to enhance resilience. This study investigates the development of resilience through counseling programs, focusing on improving stress coping skills. The research aims to evaluate the effectiveness of structured counseling interventions in enhancing individuals’ ability to manage stress and build resilience. A quantitative approach was employed using a quasi-experimental design with pre- and post-test measures. The participants consisted of 120 individuals experiencing moderate to high stress levels, divided into intervention and control groups. The intervention group participated in an 8-week counseling program that integrated cognitive-behavioral therapy (CBT) techniques, mindfulness practices, and stress management strategies. Data were collected using standardized resilience and stress-coping questionnaires, and the results were analyzed using paired t-tests and ANCOVA. The findings revealed significant improvements in the resilience and stress-coping abilities of participants in the intervention group compared to the control group (p < 0.01). Participants reported enhanced emotional regulation, problem-solving skills, and adaptability to stressors. The study concludes that counseling programs focusing on stress-coping skills are effective in fostering resilience. These findings highlight the importance of integrating such programs into mental health interventions to promote well-being and adaptability in diverse populations.